The antiproton interaction with an internal 12C target inside the HESR ring at FAIR. (April 2016) - Introzzi, R; Balestra, F; Lavagno, A; Scozzi, F; Younis, H
Abstract: In order to fulfill the goal of producing higher rates of doubly strange hyperons, the P̄ANDA collaboration will use the antiproton ring HESR at the future facility FAIR. The low energy hyperon production by an antiproton beam requires to insert a solid target inside the ring. Unwanted side effects of such an insertion are the overwhelming amount of annihilations, which would make the detectors blind, and the fast depletion of the bunch, which circulates inside the ring. The choice of the target material impacts the hyperon production yield: Carbon turned out to provide enough initial hyperon deceleration and keep secondary interactions below a tolerable level. The use of a very thin Diamond target, together with beam steering techniques, seems to be a satisfactory solution to the above problems and will be described hereafter.